Inversion Characteristics of Hydrocarbon Gases Carbon Isotopes Varying With Temperature and Implications for Shale Exploration - Wu, Yingqin; Liu, Yanhong; Wang, Tong; Wang, Zhiyu; Yuan, Longmiao; Xia, Yanqin (Frontiers in Earth Science, 2021)
In order to understand the influence of source rock type and maturity on light hydrocarbon isotope change more objectively, a closed-system pyrolysis experiment was carried out on six samples of different types from 250 ~ 550 °C. The δ13C1 values range from -73.3‰ to -29.8‰, δ13C2 from -36.3‰ to -9.5‰, and δ13C3 from -38.5‰ to -12.4‰, respectively. The range of δ13C1 was the largest, reaching 43.5‰. The results showed that the temperature has a certain effect on the carbon isotope value of pyrolysis gas. With the increase of the degree of thermal evolution, the carbon isotope value of methane in all samples, except for huangxian gangue, has a change trend from heavy to light firstly, then get heavier. In addition, the carbon isotope values of methane, ethane and propane have the features of δ13C1 < δ13C2 < δ13C3 when the temperature is below 550 °C, which are made up of a series of positive carbon isotopes. However, when the temperature reaches 550 °C, there is an inversion of the simulated gas carbon isotope values in Huangxian coal gangue, Minqin oil shale and Huaan carbonaceous shale, i. e. δ13C2 > δ13C3 and δ13C2 > δ13C1. It indicates that the secondary cracking occurred at high maturity or over maturity stage.